POLA KOMUNIKASI INTERPERSONAL PEMBIMBING HAJI DAN UMROH DALAM MEMBERIKAN PELAYANAN KEPADA CALON JAMAAH HAJI DAN UMROH DI JAYA MAS TOUR & TRAVEL - Adella Putri Najwa; Murtiadi; Andi Banus Achir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to identify and describe the interpersonal communication patterns employed by Hajj and Umrah guides in providing services to prospective pilgrims at Jaya Mas Tour & Travel. This research is motivated by the importance of interpersonal communication in creating effective services, building trust, and helping prospective pilgrims understand the procedures of Hajj and Umrah properly. The study employed a qualitative method with a descriptive approach based on the constructivist paradigm. Data were collected through observation, in-depth interviews, and documentation involving Hajj and Umrah guides as well as prospective pilgrims at Jaya Mas Tour & Travel. The data were analyzed through the processes of data reduction, data presentation, and conclusion drawing. The findings indicate that the interpersonal communication patterns implemented by the guides have been effective through the application of openness, empathy, supportiveness, positiveness, and equality, as proposed by DeVito's interpersonal communication theory. Communication was carried out both face-to-face and through digital media, enabling stronger relationships between the guides and prospective pilgrims. The communication barriers encountered included differences in age, educational background, personal characteristics, and religious understanding among the prospective pilgrims. To overcome these barriers, the guides used simple language, applied a personal approach, provided continuous assistance, and utilized communication media to ensure that information was well understood. The study concludes that effective interpersonal communication plays a significant role in improving the quality of services provided to prospective Hajj and Umrah pilgrims at Jaya Mas Tour & Travel while also enhancing pilgrims' trust and satisfaction with the services provided.